THE EFFECT OF MINIMUM WAGES ON YOUNG WORKERS IN THE FORMAL SECTOR - Sitompul, Thomson (Soedirman Economics Education Journal, 2023)
In contrast to previous studies regarding the impact of minimum wages which only focused on total workers and the economic sector and the use of employment status to form formal workers, this study analyzed the effect of minimum wages on one of the demographic variables namely youth by comparing the formation of formal workers using cross tabulation of status and type of work and formation of formal workers by using job status only. The purpose of this research is to analyze the impact of the minimum wage on young formal workers in Indonesia. This study describes that the difference in the high percentage of young formal workers supports the research objective that it is important to compare the impact of the minimum wage on the two categories. Using the 2015 SAKERNAS cross section data and the OLS regression method the impact of the minimum wage on young formal workers using cross-tabulations is higher than the impact of the minimum wage on young formal workers using only employment status. The minimum wage reduces formal youth employment (either by cross-tabulation or by status alone) significantly. Ignoring the use of cross-tabulations between status and type of work can lead to underestimates in the percentage of young formal workers so that the use of cross-tabulations is more representative in showing the effect of minimum wages on young formal workers compared to using employment status alone